Resilience across time: Longitudinal measurement invariance of the Brief Resilience Scale in French university students - Anja Todorović; Cédric Baumann; Christine Rotonda; Elise Eby; Sarah Lapcevic; Stéphanie Bourion-Bédès (PLoS ONE, 2026)
Purpose The response shift effect occurs in Patient-reported outcome measures (PROMs) as a consequence of internal changes in perception of the measured concept. The purpose of this study was to assess the potential presence of the response shift effect within the French version of the Brief Resilience Scale (BRS) in a population of university students in the Lorraine region of France. Methods To measure resilience, the French version of the BRS was used. To examine the potential presence of the response shift effect within this questionnaire, the Oort’s procedure and Rasch Measurement Theory based ROSALI-RMT algorithm was used. Results The BRS demonstrated longitudinal measurement invariance across Time 0 and Time 1, as assessed using the ROSALI algorithm. A slight but significant increase in resilience was observed over time (time effect = 0.22, p < 0.0001), with no evidence of response shift effects, suggesting that the observed changes in resilience were genuine and not influenced by recalibration. Conclusion These findings support the validity of the BRS in measuring resilience over time and highlight its utility in capturing genuine changes in resilience.